Uplink performance evaluation of wireless networks based on IEEE 802.11g and IEEE 802.11n under co-channel interference (MASKAY, 2025)
Due to their widespread use, wireless networks conforming to IEEE 802.11g/n standards can experience channel saturation, leading to interference that affects their performance. This study analyzes the performance of these networks under various interference scenarios, evaluating their behavior in terms of Quality of Service (QoS) metrics, including throughput, delay, jitter, and packet loss. Experiments were conducted in indoor environments using two standards, IEEE 802.11g/n, and different channel configurations. Initially, networks were evaluated in scenarios where all devices operated on the same channel (1, 6, or 11), creating co-channel interference. Subsequently, scenarios were analyzed where each access point operated on a different channel to minimize interference. The intrusive traffic injection technique was employed for data collection, enabling precise measurements of the analyzed metrics. The results indicate that network performance varies significantly depending on the standard used and the channel configuration. Overall, networks operating under the IEEE 802.11n standard exhibited better throughput performance but were more susceptible to interference compared to those operating under the IEEE 802.11g standard. Additionally, transmission efficiency decreased significantly in the presence of co-channel interference, with performance losses of up to 35% in some scenarios. These findings underscore the significance of effective channel planning in wireless networks, enabling optimal performance and mitigating the adverse effects of interference.
Keywords: Normalized throughput; delay; jitter; packet loss; co-channel interference; IEEE 802.11g; IEEE 802.11n